Empowering Women as Waste Bank Activists in South Tangerang City - Lusi Andriyani; Siska Yuningsi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Garbage is one of the problems in the city of South Tangerang (Tangsel). Tangsel produces approximately 880 tons of waste every day. The increase in population has an impact on increasing the volume of waste from households. One of the methods used by the Tangsel city government to reduce waste is through the waste bank program since 2012 a total of 208 Waste Banks have been formed, however, only 50 percent are active. By looking at these conditions, there needs to be efforts to empower women in reactivating waste banks in Tangsel City. One of the newly developed waste banks is the “yes” waste bank. This waste bank is located in RW 10, Cipayung Village, Ciputat District, South Tangerang. The purpose of this activity is to increase independence by empowering the potential of RW 10. The target of this PKM program is to form community awareness to sort waste, train the attitudes of RW 10 residents to have a conscious behavior in sorting waste in supporting independent waste management, developing economic skills. The method that will be applied to achieve the goals / targets of the PKM program is a combination of several approaches, namely through counseling, training, mentoring. The main outputs of this activity are: Independent waste management module, handicraft made from garbage